Scoutting Uroflometry - Kamarulzaman, Mohd Nazli; Redzuan, Muhd Zaki Azre; Hj Ghazali, Hamid (IIUM Press, International Islamic University Malaysia, 2017)
This research book was aimed to ilustrate any effect of changing voiding positions in uroflowmetry findings in patients with BPH. The study positions include standing, sitting and squatting. This is a cross section observational study of BPH patients attending to Urology Clinic Hospital Tengku Ampuan Afzan (HTAA) from March 2015 to December 2015. Uroflowmetry in standing, sitting and squatting positions was done in those fulfilling the study criteria. The maximum flow rate, average flow rate, voiding volume, total voiding time and post-voiding residual volume were measured and recorded.